Fuzz test case generation for penetration testing in mobile cloud computing applications - Al-Ahmad, Ahmad Salah; Kahtan, Hasan (Springer Nature Switzerland, 2018)
Security testing for applications is a critical practice used to protect data and users. Penetration testing is particularly important, and test case generation is one of its critical phases. In test case generation, the testers need to ensure that as many execution paths as possible are covered by using a set of test cases. Multiple models and techniques have been proposed to generate test cases for software penetration testing. These techniques include fuzz test case generation, which has been implemented in multiple forms. This work critically reviews different models and techniques used for fuzz test case generation and identifies strengths and limitations associated with each implementation and proposal. Reviewing results showed that previous test case generation methods disregard offloading parameters when generating test case sets. This paper proposes a test case generation technique that uses offloading as a generation parameter to overcome the lack of such techniques in previous studies. The proposed technique improves the coverage path on applications that use offloading, thereby improving the effectiveness and efficiency of penetration testing.